GPCRs: From Deorphanization to Lead Structure Identification - Bourne, H.; Horuk, R.; Kuhnke, J.; Michel, H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Based on the international workshop GPCRs: From Deorphanisation to Lead Structure Identification, held in Berlin in May 2006, the book highlights the following topics: Structure of GPCRs, Design of GPCR Ligands, GPCR Signalling, Deorphanization and Assay Development. All chapters are written by leading experts in the field, discussing the most recent state of the art. They give insight into the approaches taken by industry and academia to address GPCRs and depict how mature this target class-oriented research has become in the last decade. The book reflects the actual trends in the fast-emerging field of GPCR research in academia and industry.
G-Proteins and GPCRs: From the Beginning -- Modeling GPCRs -- QSAR Modeling of GPCR Ligands: Methodologies and Examples of Applications -- Privileged Structures in GPCRs -- Designing Compound Libraries Targeting GPCRs -- Orphan Seven Transmembrane Receptor Screening -- The Role of GPCR Dimerisation/Oligomerisation in Receptor Signalling -- Deorphanization of G-Protein-Coupled Receptors -- Virus-Encoded G-Protein-Coupled Receptors: Constitutively Active (Dys)Regulators of Cell Function and Their Potential as Drug Target -- Modulation of GPCR Conformationsby Ligands, G-Proteins, and Arrestins -- High Content Screening to Monitor G Protein-Coupled Receptor Internalisation -- High-Throughput Lead Finding and Optimisation for GPCR Targets.
Keywords: Medicine; Medical microbiology; Pharmacology; Chemoinformatics; Medical biochemistry; Biomedicine; Pharmacology/Toxicology.; Medical Biochemistry; Computer Applications in Chemistry; Medical Microbiology; Electronic books